Tingkat Kepuasan Konsumen Cafe 57’FU Di Kelurahan Talikuran Kecamatan Kawangkoan Utara Kabupaten Minahasa - Lomboan, Veronika Agustin; Talumingan, Celcius; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2024)
This research aims to measure the level of consumer satisfaction at Cafe 57'FU from the aspects of product, price, place, promotion and service quality. This research was conducted in August 2023. The data collection method used was primary and secondary data. Respondents in this study consisted of 50 people using accidental sampling. The data analysis used is descriptive analysis using a Likert scale. The research results show that the level of consumer satisfaction at Cafe 57'FU in Talikuran Village, North Kawangkoan District, Minahasa Regency is classified as satisfied (P), based on research results with an index of 77.33%.